Implementation of PM-UPUD Cage Management for Fattening Bali Cattle in Balangan Village, Kuwum, Mengwi, Badung - Astiti, Ni Made Ayu Gemuh Rasa; Surasmi, Ida Ayu; Yanti, Gek Dian Dharma; Wadu, Yesaya (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Cattle fattening has been done for generations, but partners want to increase its quality and quantity. Partners lack knowledge in the field of housing and feed that can be preserved, so they experience obstacles in fattening cattle. The group requested training and assistance regarding the requirements for housing for fattened bulls. Fattening bulls is a side business carried out by farmers in Kuwum village that must be preserved and maintained in each region to maintain local wisdom and the population of Bali cattle. The solution to the problems faced by partners involves applying previous research results from the proposers, which are already published, by providing appropriate technology for maintaining Bali cattle and preserving local wisdom through cattle farming. The method used is active community participation and exploration. This community service activity supports IKU 2, namely students gain experience outside the campus, and IKU 3, namely lecturers engage in activities outside the campus. The activity lasted for 10 months, involving 2 students by recognizing several courses. Contribution to Sustainable Development Goals (SDGs):·  SDG 1 – No Poverty·  SDG 2 – Zero Hunger·  SDG 8 – Decent Work and Economic Growth·  SDG 12 – Responsible Consumption and Production